THE EFFECT OF PROFITABILITY, COMPANY SIZE, AND INSTITUTIONAL OWNERSHIP ON COMPANY VALUE: (A Study of Technology Industry Companies in the Software & IT Services Sub-Sector Listed on the Indonesia Stock Exchange from 2021 to 2023) - Enggar Nursasi; M. Fariz Shevalian Arden; Munfaqiroh, Siti (Inspirasi Ekonomi : Jurnal Ekonomi Manajemen, 2025)
The purpose of this study is to analyze the influence of profitability, company size and institutional ownership on company value. This study uses a quantitative approach with multiple linear regression analysis methods. The population in this study is industrial companies in the technology sector sub-sector software and IT services in 2021-2023, with a sample of 33 using the Purposive Sampling method. The results of this study show that profitability, company size and institutional ownership influence the value of the company.